Blow-up phenomena for a quasilinear parabolic equation with inner source and nonlinear boundary condition. Issue 4 (3rd July 2016) - Yang, Rui; Bo Fang, Zhong; Yi, Su-Cheol
Abstract: In this paper, we deal with blow-up phenomena to a quasilinear parabolic equation with inner source and nonlinear boundary condition. By the technique of differential inequality, we establish a lower bound for the blow-up time if blow-up does occur. Furthermore, we consider a specific class of problems to guarantee occurrence of blow-up and derive an upper bound for the blow-up time.